Intellectual Disability and Psychotherapy : The Theories, Practice and Influence of Valerie Sinason - Corbett, Alan; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
Intellectual Disability and Psychotherapy: The Theories, Practice and Influence of Valerie Sinasoncharts the transformative impact of the noted psychotherapist s work with children and adults with intellectual disabilities upon both a generation of clinicians and the treatment and services delivered by them. Examining how contemporary Disability Therapists have discovered, used and adapted such pioneering concepts as the Handicapped Smile and Secondary Handicap as a Defence Against Trauma in their clinical work, the book includes contributions from renowned practitioners and clinicians from around the world. It shines a light on how Sinason s work opened doors for working with people who were previously thought of as unreachable. IntellectualDisability and Psychotherapy will be an essential resource to anyone working with children or adults with disabilities, as well as psychotherapists interested in exploring Valerie Sinason s work.
Contents -- Notes on contributors -- Foreword by SUSIE ORBACH--Introduction--ALAN CORBETT--Including the excluded: Valerie Sinason, psychoanalytic pioneer --GRAEME GALTON -- Creativity and the analytic condition: creative arts approaches within a psychoanalytic frame -- EIMIR McGRATH -- We are who we see looking back at us: Valerie as a supporter of a developing organisation--ALAN CORBETT and TAMSIN COTTIS -- The handicapped smile: language and identity--LIZ LLOYD--Death, loss, and the struggle for non-disabled grief--NOELLE BLACKMAN -- Forensic groupwork and --Books Beyond Words: Valerie Sinason as colleague, co-author, and friend--SHEILAHOLLINS -- The best of both worlds: the making of a disability psychiatrist--GEORGINA PARKES -- Building insight and changing lives: the contribution of Valerie Sinason to the history of disability psychotherapy -- DAVID ODRISCOLL -- Sharing our history, informing our future: Valerie Sinason and the development of training for frontline care workers and therapists--PAT FRANKISH -- Secondary handicap and a model for the supervision of nurses--SHULA WILSON -- Labels, death-making and an alternative to Social Role Valorisation: Valerie Sinasons influence on my work--JAN WALMSLEY -- Valerie Sinason, South Africa, and the politics of seeing--LESLIE SWARTZ--Like an owl in a tree: learning from Valerie Sinason in treating patients intellectual disabilities in Sweden--ANDERS SVENSSON--Valerie Sinason and the psychodynamics of bravery --BRETT KAHR -- An interview with Valerie Sinason reflecting on her life and the evolution of disability psychotherapy--ALAN CORBETT.
Includes bibliographical references and index.
Also available in print format.
Keywords: ntellectual disability; Intellectual Disability -- psychology; Intellectual Disability -- therapy; Psychotherapy -- methods; Intellectual disability; disability; influence; intellectual; psychotherapy; theories; valerie sinason; Electronic books